Characterization and Color Fastness Study of Cotton Fabric Dyed Using Coupled Natural Dyes from Tegeran Wood (Maclura cochinchinensis) and Turmeric (Curcuma longa): Karakterisasi dan Ketahanan Luntur Kain Katun yang Diwarnai Menggunakan Kopling Zat Warna Alami Kayu Tegeran (Maclura cochinchinensis) dan Kunyit (Curcuma longa) - Haris, Muhammad Naoval; Ariyanto, Randitya Teri (Balai Besar Standardisasi dan Pelayanan Jasa Industri Kerajinan dan Batik, 2026)
Growing environmental awareness has encouraged the development of sustainable textile dyeing systems based on natural colorants. Tegeran wood (Maclura cochinchinensis) and turmeric (Curcuma longa) are yellow natural dye sources containing flavonoids (morin) and curcuminoids (curcumin) with conjugated chromophore systems. This study aimed to characterize cotton fabric construction and evaluate washing and rubbing fastness of fabrics dyed using single and coupled dye extracts. An experimental quantitative approach was applied, including fabric structural characterization (72 EPI × 59 PPI; 78.5 g/m²; yarn count and crimp analysis), mordanting with Al³⁺, Fe²⁺, and Ca²⁺, dyeing at 28°C for 60 minutes, and fastness testing according to ISO 105-C06 and ISO 105-X12 standards. Color evaluation was conducted using the CIELAB system (L*, a*, b*) and total color difference (ΔE, CIE76). Results indicated that Fe²⁺ mordanting produced lower L* values and olive shades due to metal–dye coordination complex formation, whereas Al³⁺ maintained brighter yellow tones with higher b* values. The coupled dye system demonstrated synergistic chromophore interactions with controlled color variation (ΔE 13.19–32.81). Washing and rubbing fastness significantly improved in mordanted coupled systems (grade 4–5) compared to non-mordanted samples (grade 2–3). The study suggests that coupled natural dye systems with appropriate metal mordants enhance chromatic stability and fastness performance on lightweight cotton fabrics.